One-pot microemulsion synthesis of luminescent core@shell lanthanide-doped nanoparticles - Benoit Richard; Jérémie Asselin; Denis Boudreau; Emilie Ringe; Anna M. Ritcey (APL Materials)
The optical properties of lanthanide-doped nanoparticles depend on the location of dopant ions. Doped (H3O)Y3F10@(H3O)Y3F10 core@shell nanoparticles were synthesized in a one-pot inverse microemulsion involving multiple additions of precursors, leading to the isolation of the lanthanide ions in the core or the shell. This synthesis provides excellent control of shell growth without secondary nucleation. Elemental analysis, electron microscopy, and electron spectroscopy revealed the doping level and ion localization. Heavier lanthanide ions, such as Er3+, can completely replace Y3+ in the host matrix (H3O)Y3F10 without crystal structure modification; (H3O)Er3F10 can be prepared either as a shell or a core material. Lighter lanthanide ions, such as Eu3+, however, are only tolerated in the (H3O)Y3F10 matrix up to ∼15%. Eu-doped (H3O)Y3F10 nanoparticles show well-defined emission spectra, consistent with high crystallinity. The emission intensity varies with Eu doping levels, even after normalization for Eu content. The addition of an undoped shell to Eu-doped cores increases luminescence, which varies significantly with the core doping level. Luminescence decay curves, fitted as biexponentials, yield lifetimes on the order of 2 and 4 ms. For 5% Eu cores, the relative contribution of the shorter lifetime to overall emission decreases upon the addition of an undoped shell, consistent with the protection of emissive surface sites from environmental quenching. Even with uniform, well-defined shells, lighter lanthanide dopant segregation is hampered by potential ion migration. This work demonstrates not only the importance of developing syntheses permitting the controlled localization of doping ions but also the necessity of validating ion distribution in nanoparticles.